PENGARUH PERPUTARAN MODAL KERJA, PERSEDIAAN, DAN TOTAL ASET TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BEI (2017-2022) - Sebastian, Novianto; Jusuf, A An Arief (Universitas Widya Kartika Surabaya, 2024)
This study aims to analyze the influence of working capital turnover, inventory turnover, and total asset turnover on profitability in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2022. The research method used is quantitative with secondary data obtained from the annual financial reports of food and beverage subsector companies listed on IDX. Purposive sampling technique was used, and the data were analyzed using SPSS version 23. The results showed that working capital turnover and inventory turnover negatively affect profitability with significance values of 0,016 and 0,017, respectively, while total asset turnover does not significantly affect profitability with a significance value of 0,915.